Antimicrobial activity of Cymbopogon citratus (Poaceae) essential oil on Streptococcus mutans biofilm and cytotoxic effect on keratinocytes and fibroblasts - Ortega Cuadros, Mailen (2018)
Dental caries is a pathology of multifactorial origin and currently natural products are an efficient alternative treatment; The work sought to evaluate the antimicrobial activity of the Cymbopogon citratus essential oil and the citral and myrcene components against Streptococcus mutans ATCC UA159, as well as their cytotoxicity on keratinocytes and human fibroblasts. The viability effect against Streptococcus mutans on biofilms was evaluated through exposure to the three substances by using the MBEC technique-high-throughput at concentrations of 1, 0.1, and 0.01 µg/mL and chlorhexidine as positive control. The cytotoxicity of the compounds was evaluated on keratinocytes and fibroblasts through the MTT reduction technique, using 0.5 mM H2O2 as cell-death control (negative control) and ethanol 1% as vehicle control (positive control). The three substances evaluated had effects on the viability of Streptococcus mutans with mortality between 74% and 96%, without significant difference among them (p > 0.393); additionally, no cytotoxicity was evident on keratinocytes and fibroblasts in a 24-h treatment. The substances evaluated showed significant antimicrobial effects; hence, these should be studied further as potential co-adjuvants to prevent dental caries that cause minor adverse effects